LSK Derived LSK– Cells Have a High Apoptotic Rate Related to Survival Regulation of Hematopoietic and Leukemic Stem Cells - Peng, Cong; Chen, Yaoyu; Shan, Yi; Zhang, Haojian; Guo, Zhiru; Li, Dongguang; Li, Shaoguang (PLOS ONE, 2012)
A balanced pool of hematopoietic stem cells (HSCs) in bone marrow is tightly regulated, and this regulation is disturbed in hematopoietic malignancies such as chronic myeloid leukemia (CML). The underlying mechanisms are largely unknown. Here we show that the Lin−Sca-1+c-Kit- (LSK−) cell population derived from HSC-containing Lin−Sca-1+c-Kit+ (LSK) cells has significantly higher numbers of apoptotic cells. Depletion of LSK cells by radiation or the cytotoxic chemical 5-fluorouracil results in an expansion of the LSK− population. In contrast, the LSK− population is reduced in CML mice, and depletion of leukemia stem cells (LSCs; BCR-ABL-expressing HSCs) by deleting Alox5 or by inhibiting heat shock protein 90 causes an increase in this LSK− population. The transition of LSK to LSK− cells is controlled by the Icsbp gene and its downstream gene Lyn, and regulation of this cellular transition is critical for the survival of normal LSK cells and LSCs. These results indicate a potential function of the LSK− cells in the regulation of LSK cells and LSCs.